Petite histoire des musiques afro-montréalaises - Villefranche, Robert; Bernard, Yves (MUSICultures, 1989)
Robert Villefranche and Yves Bernard describe the history of Montreal musicians of African descent, telling of the formation of various groups that performed at community events and festivals and became more widely known through recordings and festivals.